2011
DOI: 10.1002/ejoc.201001452
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stereoselective Synthesis of Spiropyrazolones

Abstract: The synthesis of spiro compounds through a Michael–Michael–aldol reaction is reported. The reaction affords spiropyrazolone derivatives in good yields, in almost diastereo‐ and enantiopure form, and is catalyzed by diphenylprolinol derivatives. The reaction showed strong nonlinear effects. Remarkably, when a catalyst with 70 % ee is used, the reaction still affords the final spiro compound in almost diastereo‐ and enantiopure form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(41 citation statements)
references
References 48 publications
0
41
0
Order By: Relevance
“…In the exploration of the reaction scope, various aromatic substituents and aliphatic substituents at the C=C double bond of pyrazolones were tolerated, but aliphatic ones resulted in comparatively low reactivity because of side reactions. Highly bulky substituent at the 5‐position of unsaturated pyrazolones can limit the reaction, which has been observed in their previous reseach . Enolizable aldehydes containing bulky substituents required high reaction temperatures (60 °C) without incurring loss of diastereo‐ and enantioselectivities.…”
Section: Organocatalytic Asymmetric Synthesis Of Spiropyrazolones Fusmentioning
confidence: 95%
See 1 more Smart Citation
“…In the exploration of the reaction scope, various aromatic substituents and aliphatic substituents at the C=C double bond of pyrazolones were tolerated, but aliphatic ones resulted in comparatively low reactivity because of side reactions. Highly bulky substituent at the 5‐position of unsaturated pyrazolones can limit the reaction, which has been observed in their previous reseach . Enolizable aldehydes containing bulky substituents required high reaction temperatures (60 °C) without incurring loss of diastereo‐ and enantioselectivities.…”
Section: Organocatalytic Asymmetric Synthesis Of Spiropyrazolones Fusmentioning
confidence: 95%
“…In 2011, they conducted Michael/Michael/aldol reaction catalyzed by secondary amine catalyst Cat. 16 (20 mol %) in the presence of benzoic acid (BA) additive (20 mol %) between pyrazolone substrates 8 and unsaturated aldehyde substrates 9 with different substituents (Scheme ) . The corresponding adducts 51 were formed in moderate to good yields (55‐84 %) with 4.5 : 1 to 25 : 1 dr value and 92 to >99 % ee value, although reactions cannot proceed smoothly when the 3 position (R 1 ) substituted by bulky or highly electron‐withdrawing substituents.…”
Section: Organocatalytic Asymmetric Synthesis Of Spiropyrazolones Fusmentioning
confidence: 99%
“…for the synthesis of spiro compounds [9][10][11]. In view of the biological importance of spirocycles and in continuation of our effort on the synthesis of new spirocyclic derivatives [12,13], a new spirocyclic derivative was synthesized and characterized.…”
Section: Open Accessmentioning
confidence: 99%
“…[25] On the other hand, there are only a few literature reports for the organocatalytically asymmetric synthesis of spiropyrazolone derivatives. In 2011, Rios et al reported that spiro[cyclohexenecarbaldehyde-pyrazolones] bearing three or four contiguous chiral centers could be synthesized in a highly enantioselective manner through domino Michael/Michael/aldol/dehydration sequences between pyrazolones and enals [26] or between unsaturated pyrazolones, enolizable aldehydes, and enals catalyzed by secondary amine catalysts. [27] To the best of our knowledge, divinyl ketones as latent electrophilic acceptors, aided by asymmetric organocatalysis, have only come to be exploited this year.…”
Section: Introductionmentioning
confidence: 99%